Identification of energy consumption and energy saving potentials of electric drive systems - Javied, Tallal; Kreitlein, Sven; Esfandyari, Alireza; Franke, Jörg (Applied Mechanics and Materials, 2014)
This paper provides an overview of different types of motor systems and several measurement principals in order to determine the electricity usage of these motors. It focuses on the measurement of electric values of different drive systems. A concept of rough analysis using software or excel based tools is discussed, which argues that it is a lot easier, efficient, and cost effective to first pin point the main electricity consumers and then initiate a fine analysis of these selected systems before a cost and time intensive process of measuring every single drive system is undertaken. To achieve this, a simple and systematic process is illustrated in this paper, which can be used to identify the energy saving potential of drive systems without requiring expensive hardware.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Energy efficiency; Energy management; Energy measurement